Pengembangan Bahan Ajar PAI Berbasis Digital Menggunakan VAK Method melalui Smart Card ASWAJA An-Nahdliyah (SCAN) di TK MNU 16 Mayor Damar Turen - Husni, Muhammad; Rohanita, Lailatur (AS-SABIQUN, 2026)
The integration of technology into Islamic Religious Education (Pendidikan Agama Islam, PAI) learning for early childhood is an urgent necessity amid changes in the educational ecosystem in the digital era, yet its implementation still faces challenges in maintaining alignment between technological innovation, Islamic values, and children’s developmental characteristics. This study aimed to analyze the effectiveness of a technology-based PAI learning model adapted within the context of an Aswaja An-Nahdliyah-oriented institution at TK Muslimat NU 16 Mayor Damar Turen, with a focus on its support for the holistic development of learners. The study employed a descriptive qualitative approach with a case study design; data were collected through observation, in-depth interviews, documentation, and field notes, and were analyzed using the Miles and Huberman model. The findings indicate that the use of digital media—such as interactive videos, Islamic applications, digital storytelling, animated stories of prophets, Smart Hafiz, and Smart Card Aswaja—had a positive impact on children’s cognitive, affective, and psychomotor development. Children were better able to understand basic Islamic concepts, displayed emotional responses aligned with the moral values of the stories, and more accurately imitated worship movements. However, the implementation of this model has not yet been fully optimal due to limited devices, variation in teachers’ digital literacy, and the high potential for visual distractions among children. This study concludes that the technology-based PAI learning model is effective insofar as the use of media is curated through pedagogical approaches that are sensitive to Islamic values and children’s developmental stages. The implications are that educational institutions need to strengthen teachers’ religious digital literacy, enhance technological infrastructure, and develop developmentally appropriate PAI media so that technology integration proceeds in a sustainable and transformative manner.